A NEW VIEW ON THE DRIVING MECHANISM OF MILANKOVITCH GLACIATION CYCLES - Liu H.S. (My University, 1995)
Dynamical instabilities in the glaciation and deglaciation of the ice sheets can be triggered by pulsations of the rate of change of the orbital and rotational parameters. The purpose of this paper is to demonstrate that the Milankovitch glaciation cycles are extremely sensitive to the rate of change of the obliquity frequency. The first of our three contributions is a pedagogic principle of dynamical instability which provides a scientific basis for the driving mechanism of the glaciation cycles. The second contribution is a clarification of the origin and climate significance of the obliquity related 100 kyr cycle in terms of nonlinear coupling between various orbital and rotational parameters. Finally, the fluctuations in the size of the ice sheets are computed using the Weertman-Birchfield-Watts model of ice sheets. It is demonstrated that the growth and decay of the width of the ice sheets are in good agreement with the variations in the continental ice volume as seen in the late Pleistocene δ18O record.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен